DdPCR-based detection of circulating tumour DNA from paediatric high grade and diffuse midline glioma patients. (27th January 2021) - Izquierdo, Elisa; Proszek, Paula; Pericoli, Giulia; Temelso, Sara; Clarke, Matthew; Carvalho, Diana M; Mackay, Alan; Marshall, Lynley V; Carceller, Fernando; Hargrave, Darren; Lannering, Birgitta; Zdenek, Pavelka; et al.
Abstract: Background: The use of liquid biopsy is of potential high importance for children with high grade (HGG) and diffuse midline gliomas (DMG), particularly where surgical procedures are limited, and invasive biopsy sampling not without risk. To date, however, the evidence that detection of cell-free DNA (cfDNA) or circulating tumour DNA (ctDNA) could provide useful information for these patients has been limited, or contradictory. Methods: We optimised droplet digital PCR (ddPCR) assays for the detection of common somatic mutations observed in paediatric HGG/DMG, and applied them to liquid biopsies from plasma, serum, cerebrospinal fluid (CSF) and cystic fluid collected from 32 patients. Results: Although detectable in all biomaterial types, ctDNA presented at significantly higher levels in CSF compared to plasma and/or serum. When applied to a cohort of 127 plasma specimens from 41 patients collected from 2011-2018 as part of a randomised clinical trial in pediatric non-brainstem HGG/DMG, ctDNA profiling by ddPCR was of limited use due to the small volumes (mean=0.49ml) available. In anecdotal cases where sufficient material was available, cfDNA concentration correlated with disease progression in two examples each of poor response in H3F3A _K27M-mutant DMG, and longer survival times in hemispheric BRAF _V600E-mutant cases. Conclusion: Tumour-specific DNA alterations are more readily detected in CSF than plasma. Although we demonstrate the potential of the approach to assess tumour burden, our results highlight the necessity for adequate sample collection and approaches to improve detection if plasma samples are to be used.